Chapter 10 Avanços nas humanidades digitais - Marquilhas, Rita (De Gruyter, 2016)
This handbook provides a general yet detailed account of the current research in Portuguese linguistics by combining overview chapters and in-depth analyses of selected topics. It integrates diachronic and synchronic, standard and dialectal, adult grammar and L1 acquisition data, and offers comprehensive information on specific features of Portuguese, using the methods, insights and comparative orientation of present-day linguistic research.